ASSESSMENT METHODS AND TREATMENT OF ODONTOGENIC PHLEGMONS IN CHILDREN: CLINICAL FEATURES AND MANAGEMENT - Akhmedov Ilhom Ibrahimovich (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract Odontogenic phlegmon is a serious purulent infection of the maxillofacial region that originates from dental sources. In pediatric patients, the clinical course, diagnosis, and  treatment  require  special  attention  due  to  the  anatomical  and  immunological features  of  children.  This  paper  discusses  the  clinical  presentation,  diagnostic approaches,  and  therapeutic  strategies  for  managing  odontogenic  phlegmon  in children.